Prussian Blue‐Type Electrodes: Over 2 V Aqueous Sodium‐Ion Battery with Prussian Blue‐Type Electrodes (Small Methods 4/2019). Issue 4 (9th April 2019) - Nakamoto, Kosuke; Sakamoto, Ryo; Sawada, Yuki; Ito, Masato; Okada, Shigeto
Abstract : In article number1800220, Shigeto Okada and co‐workers develop a battery with high operational voltage of over 2 V and high rate performance, which are achieved by a novel aqueous sodium‐ion battery with the combination of an open‐framework Prussian blue‐type sodium manganese hexacyanoferrate cathode, and an open‐framework Prussian blue‐type potassium manganese hexacyanochromate anode. This is in conjunction with a highly concentrated and electrochemically stable sodium perchlorate aqueous electrolyte.